Design of A Vertical Conveyor System for Scrap Rubber in FGV Felda Rubber Industry - KERK, TECK SENG; azlan, mohd azwir (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The vertical conveyor system is a mechanical system that can be used to convey the product from a level to another level. In FGV Rubber Industry, the manual conveying method is costly and low productivity. Therefore, this project aims to design a conveyor system that could help the requestor to achieve the expected daily production capacity as requested by the industry. The whole design process stage of the conveyor system was modified by referred to the Pahl & Beitz design process while the design analysis of the screw conveyor system was referred to the engineering guide from KWS Manufacturing Company. In this project, the designed machine was focused on the requirement listed by the requestor and fulfill the technical needs of the industry. The simulation and project drawings were outlined and determined by SolidWorks software. The production capacity of the designed machine is approximately 107.69 tons/hr.